Good agreement between parents and physician in the assessment of ear discharge in children - van Dongen, Thijs M A; Schilder, Anne G M; Manders, Lieke A; van der Veen, Erwin L; van der Heijden, Geert J M G (The Pediatric infectious disease journal, 2012)
Physicians often rely on parental observation of ear discharge in the follow-up after its treatment, but little is known about the reliability of this assessment. Follow-up data of trial participants treated for acute or chronic ear discharge showed a good agreement between parents' and physician's assessment, with high positive predictive values, but lower negative predictive values.